1996
DOI: 10.1046/j.1365-2125.1996.42013.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of vagus‐mediated pancreatic polypeptide release by the μ‐opiate receptor agonist loperamide in man

Abstract: 1Morphine suppresses the release of pancreatic polypeptide, a hormone under vagal cholinergic control. The intention of the study was to detect whether the μ‐opiate receptor agonist loperamide is also able to inhibit pancreatic polypeptide release, and to define its site of action. 2In groups of healthy subjects (n=6 each) stimulation of pancreatic polypeptide was assessed in five different tests: (i) insulin‐hypoglycaemia; (ii) modified sham feeding; (iii) intravenous infusion of the cholecystokinin analogue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…The effect on diarrhea is primarily due to an inhibition of intestinal secretion and gut motility [10]. The mechanism of pancreatic injury is thought to be by two different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect on diarrhea is primarily due to an inhibition of intestinal secretion and gut motility [10]. The mechanism of pancreatic injury is thought to be by two different mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Being an opiate it probably causes a spasm at the sphincter of Oddi in a similar waytomorphine. A study on 6 healthy people has shown that loperamide causes dose-dependent inhibition of pancreatic polypeptide release mediated by vagal-cholinergic pathways [10]. The pancreatic polypeptide suppresses the secretion from exocrine pancreas, and it has been proposed that it most likely increases exocrine pancreas secretion [9].…”
Section: Discussionmentioning
confidence: 99%
“…11 The l-opiate receptor agonist loperamide blocked bethanechol-induced gallbladder contraction in the current study, and it has previously been shown to inhibit CCK-induced gallbladder contraction in humans. 5 A direct effect of opiate peptides -mediated by opiate receptors -on pancreatic cells was excluded. 22 The findings reported here are consistent with the results of Guarraci et al 11 showing that opioid agonists have a potent inhibitory effect on gallbladder motility by decreasing the release of Ach and other excitatory neurotransmitters in guinea-pigs.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our present results demonstrating a loperamide-mediated decrease in neurally mediated gallbladder emptying, we described a loperamide-mediated inhibition of vagal function after corticotrophin-releasing hormone (CRH) injection, modified sham-feeding and insulin hypoglycaemia testing, while peripheral atropine-like cholinergic actions, like PP release upon bethanechol infusion, were unaffected. 5 A direct effect of opiate peptides -mediated by opiate receptors -on pancreatic cells was excluded. 26 An influence of loperamide on vagal afferents cannot be excluded, as l-opiate receptors have been detected in presynaptical parts of vagal afferents 27 and mesenteric afferent fibres are markedly stimulated by l-opioid receptor agonists -an effect blocked by l-opiate antagonist alvimopan.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation